Impact of pre-slaughter transport conditions on stress response, carcass traits, and meat quality in growing rabbits. (December 2018) - Trocino, Angela; Zomeño, Cristina; Birolo, Marco; Di Martino, Guido; Stefani, Annalisa; Bonfanti, Lebana; Bertotto, Daniela; Gratta, Francesco; Xiccato, Gerolamo
Abstract: In growing rabbits ( n = 320; 84 d of age), an increase in the journey duration to the slaughterhouse from 1 h to 3 h under mild climatic conditions (10–13 °C; 75–90% relative humidity) affected several stress indicators in the plasma and muscle collected at slaughter (cortisol; corticosterone; lactate dehydrogenase, LDH; lactate; heat shock protein 70 kDa, HSP70; osmolality, and Na) (0.001 < P < .05), reduced muscle L*, b* ( P < .01), and meat shear force ( P < .05), and increased the dressing out percentage and muscle pH ( P < .01). An increase in the lairage duration before slaughtering from 30 min to 3 h affected muscle cortisol and plasma creatinine kinase, LDH, lactate, and HSP70 (0.001 < P < .05), increased dressing out percentage and muscle pH ( P < .05), but decreased meat shear force ( P < .001). The interaction between journey and lairage duration was significant for several stress indicators and meat quality. Highlights: The transport process causes stress in rabbits. Transportation time should be minimized in view of animal welfare. Both journey and lairage duration may affect meat quality traits. Crate distribution inside the truck plays a minor role.